The place of delta neutrophil index (immature granulocyte) and hematological markers in diagnosing pediatric acute appendicitis (Annals of Medical Research, 2023)
Aim: It is aimed to reveal the importance of markers such as inflammation markers, c-reactive protein, complete blood count parameters (white blood cell, neutrophil lymphocyte ratio, platelet lymphocyte ratio), delta neutrophil index (immature granulocyte), which play a role in acute appendicitis pathology and progression, in the diagnosis of pediatric acute appendicitis, and the relationship between these markers.Materials and Methods: 47 patients who applied to Kahramanmaraş Sütçü İmam University Medical Faculty Hospital between 01.01.2019 and 31.08.2022 due to acute appendicitis were included in the study. Demographic and medical information of the patients were obtained by examining the hospital automation system.Results: In the diagnosis of acute appendicitis in pediatric patients, delta neutrophil index, neutrophil lymphocyte ratio and platelet lymphocyte ratio, which are inflammatory markers, were found to be statistically significantly higher. It was stated that delta neutrophil ındex, white blood cell, neutrophil lymphocyte ratio and platelet lymphocyte ratio measurement are easily accessible blood parameters without requiring additional cost to the health system, as they are worked automatically within the parameters of the complete blood count.Conclusion: We recommend the use of delta neutrophil index, neutrophil lymphocyte ratio and platelet lymphocyte ratio values along with physical examination, imaging studies, and laboratory tests to assist in the diagnosis of pediatric acute appendicitis patients.
Keywords: Acute appendicitis; Delta neutrophil index; Neutrophil lymphocyte ratio; Platelet lymphocyte ratio